1998
DOI: 10.1108/01425459810247297
|View full text |Cite
|
Sign up to set email alerts
|

Unfair dismissal cases, disciplinary procedures, recruitment methods and management style

Abstract: IntroductionAgainst the background of recent and current proposals in the UK for changes in unfair dismissal legislation, this paper reports on recent company/site level research into the factors influencing the incidence, or otherwise, of unfair dismissal cases. The research is based on matched comparisons of predominantly small businesses or sites in three industries. This paper seeks to review disciplinary procedures in these companies, and to examine some of the major influences on their operation, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 2 publications
(2 reference statements)
3
29
0
Order By: Relevance
“…Moreover, these frameworks lead to changes in practice. Our study, for example, confirms that environmental regulation leads to better environmental procedures and practices, while the study by Goodman et al (1998) revealed that legislation led to formal employment disciplinary procedures. Similarly, Vickers et al (2005) showed that SMEs had a range of responses to health and safety legislation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, these frameworks lead to changes in practice. Our study, for example, confirms that environmental regulation leads to better environmental procedures and practices, while the study by Goodman et al (1998) revealed that legislation led to formal employment disciplinary procedures. Similarly, Vickers et al (2005) showed that SMEs had a range of responses to health and safety legislation.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies, as Edwards et al (2004) have shown, rely upon owner-manager perceptions of regulation which are frequently overstated and not based on concrete experience. Notwithstanding these limitations, a number of studies have revealed that regulation induces compliance (Druker et al, 2005;Goodman et al, 1998;Patton and Worthington, 2003;Petts et al, 1999;Vickers et al, 2005). Importantly, studies have also revealed that regulation does not induce behaviour that goes beyond compliance in the form of modernisation and cultural change (Edwards et al, 2004;Patton and Worthington, 2003;Petts et al, 1999).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, the influence of owner-managers in these cases was an important variable that weakened the extent of employee input. This was deemed to be predicated on a unitarist notion that 'what is good for the business is assumed to be good for employees' (Goodman et al, 1998). The net effect was minimal information and consultation with an acquiescent and satisfied workforce.…”
Section: Union Stewardmentioning
confidence: 99%
“…Rather than derecognise unions or substitute collective consultation for non-union employee representation, management seek to control information and consultation structures. This also draws on the sophisticated paternalist (unitarist) managerial philosophy of 'what is good for the business is assumed to be good for workers' (Goodman et al, 1998).…”
Section: A Conceptual Framework To Evaluate the Dynamics Of Employee mentioning
confidence: 99%